The Linguistic Packaging of Emotion: Functional Stylistic Strategies in Trilingual Advertising Slogans - Karimova Ominaxon Maxmudovna; Arustamyan Y. Y (Peerian Journals Publishing, 2025)
In the context of Uzbekistan’s multilingual marketing, this article examines the linguistic and stylistic techniques employed to translate emotional content in advertising slogans between English, Russian, and Uzbek. Emotional resonance is an important persuasive component of global branding, but because of variations in audience expectations, stylistic conventions, and cultural norms, its cross-linguistic transfer is still difficult. The study compares the official or widely used Russian and Uzbek translations of ten international brand slogans with their original English versions using a qualitative stylistic analysis. The study identifies common translation techniques, such as modulation, adaptation, ellipsis, and metaphorical substitution, by referencing to Skopos Theory, Koller’s equivalency framework, and the concepts of functional and dynamic equivalence. The findings show that functional adaptation preserves emotional tone better than formal or literal translation. The analysis also emphasizes how rhetorical devices such as metaphor, tone, rhythm, and others are used to linguistically encode emotion. These devices are then reformulated in the target languages to preserve their affective impact. The results highlight the translator’s function as a cultural mediator who balances linguistic structure and emotional intent. By providing a framework for examining emotional translation in trilingual advertising contexts and guiding future localization techniques, this study advances the fields of translation studies and marketing communication
Keywords: Emotional translation; stylistic adaptation; advertising slogans